(untitled) (Research, Society and Development, 2022)
Objective: Report the experience about the updating of the Elder’s Health Book, in an Elder’s Support Group of a Basic Health Unit located in the municipality of Niterói/RJ. Method: Experience report taken in the first semester of 2022, about the participation on the Elder’s Health Book in the coexistence group of a health unit, organized by the unit’s professionals and the nursing academics of the 6th semester of the Universidade Federal Fluminense (UFF). Results and discussion: The activity with the elders group, had present, the nursing academics, to perform the update of the Elder’s Health Book. The service was carried out in order of arrival, and, at the consultation, the elders were oriented about the health book’s functionality, its importance and usefulness. The consultation, as well as the monitoring of the user’s routine, allowed an approximation between the professional and the elderly, and through active listening, it was possible to perform the multidimensional evaluation, enabling the identification of the vulnerabilities and individualities of each patient, enabling a humanized care and health promotion. Conclusions: The participation experience in the coexistence group allowed for a direct and individual contact with the patient, and promoted autonomy in the consultation, stimulating the confidence of the students on the nurse-patient relationship. Therefore, the importance of correctly filling out all the information collected in the Elder’s Health Book and of their multidimensional assessment, providing an adequate care according to the needs of each patient, strengthening the bond between the healthcare unit and the population.